A New Species of the Bokermannohyla martinsi Group from Central Bahia, Brazil with Comments on Bokermannohyla (Anura: Hylidae) - Faivovich, Julián (2009)
A new species of the Bokermannohyla martinsi group is described from Chapada Diamantina, State of Bahia, northeastern Brazil. It is differentiated from the other two species in the group by the combination of slender body (quite robust in B. langei and B. martinsi), non-bifid distal prepollex (bifid in B. langei and B. martinsi), squared shape of the posterior portion of the distal prepollex (pointed process in B.langei and B. martinsi), large size and lateral inclination of the tympanum (quite reduced in B. langei, almost parallel to the longitudinal axis in both B. langei and B. martinsi), absence of dark bars in hidden areas of thighs (dark bars present on anterior, dorsal and posterior surfaces of thighs in B. martinsi), and shape of the supratympanic fold. We report for the first time the occurrence of a mental gland in 16 species of Bokermannohyla.